High Connectivity in Spatial Design: Spatial Configuration Analysis Using Space Syntax - Faqihuddin, Muhammad Imam; Maulana, Rizqi; Musaddad, Muhammad Rafi; Jasim, Maulana Izzuddin (International Journal of Environment, Architecture, and Societies, 2025)
The spatial configuration of a building plays a crucial role in facilitating daily activities. Previous research has demonstrated that the layout of spaces within a building significantly affects the level of connectivity between rooms. Moreover, existing studies tend to provide recommendations in the form of entirely new spatial designs that differ significantly from existing conditions, thereby reducing the likelihood of successful implementation. The Megawati Soekarnoputri Building at UIN Maulana Malik Ibrahim Malang serves as an intriguing case study for this research due to the varying complexity and spatial characteristics across its different floors. In this study, the Space Syntax method is employed to analyze the connectivity between spaces within the building to demonstrate that the proposed recommendations can optimally preserve existing conditions while effectively enhancing spatial connectivity, thereby making them more feasible for practical implementation. The findings reveal that floors with more rooms and clearly defined physical barriers tend to exhibit lower levels of connectivity. Conversely, floors with fewer rooms generally display higher connectivity. This indicates that to enhance connectivity between spaces, barriers do not necessarily have to be solid physical dividers (such as walls), but could be represented by unique visual cues such as colors or distinctive signs.